Sole companies: analysis and feasibility in Iran and the United States of America: Empresas únicas: análisis y viabilidad en Irán y Estados Unidos de América - Narimani, Bagher; Lotfi, Alireza; Bashokooh, Mozaffar (Political Questions, 2022)
The purpose of the article was to analyze the legislation governing sole proprietorships in Iran. Although the new draft commercial law and the existing laws in European and American companies indicate the possibility of forming a sole proprietorship, it is not possible in Iran to form a sole proprietorship under the existing regulations, especially the existing commercial law. Methodologically in the essay, based on a comparative study on American commercial law and through analytical issues, we point out that, from the analytical (not legal) point of view, the formation of such corporations not only does not face any strong obstacles, but also, it can be beneficial in various ways. We then present the benefits of the Single Corporation and finally discuss the administration and liquidation of these Corporations. Everything allows us to conclude that, the idea of forming a sole corporation is unusual in Iran, but it is also accepted by the state-owned companies. Therefore, the Iranian legislator can develop this idea and apply it to private business enterprises. However, it is noted that permission to run such companies should be considered while ensuring the rights of third parties.